Новый подвид ящурки Штрауха — Eremias strauchi kopetdaghica ssp. n. (Sauria, Reptilia) из Туркмении - Щербак, Н.Н (Вестник зоологии, 1972)
As a result of field observations and laboratory treatment of 88 samples of Eremias
strauchi Kessle r a considerable difference in the samples from Transcaucasia and
Turkmenia was established. A subspecies was described, distributed in Kopet-Dag and
North-Eastern Iran, differing from nominal form from Transcaucasia and North-Western
Iran in less amount of back scales, in transversal raw, threat scales, femoral pores, abdominal scales, scales round the 9th — 10th tail ring and also in some other features.